Microstrip bandpass filter using triangular patch resonator for wimax applications - Abdul Rahman, Mohd Ridzuan (2013)
Filters are essential in communication systems nowadays. They are usually used to select frequencies. Filters are playing an important role to select or confine the Radio Frequency (RF) signals within assigned spectral limits since the electromagnetic spectrum is limited by licensing issues and shared over different channels. A compact bandpass filter (BPF) using Triangular Patch Resonator is designed. A 5.5GHz dual-mode microstrip BPF has been introduced. In order to simulate the BPF performance with different configurations, a series of simulations based on Sonnet Lite will be used to run the simulation. Result has been analyzed in terms of reflection coefficient and transmission coefficient. The simulated filter performances are presented.